Optimalisasi Sistem Operasi dan Harga Jual untuk Kontinyuitas Usaha Kerupuk Singkong Sadariyah “Mbah Juki” Blitar - Fiernaningsih, Nilawati; Himmah, Mahmudatul; Zubaidi, Zubaidi; Takwim, R N Akhsanu; Junus, Mochammad; Widayani, Anna; Ismanto, Ismanto (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The community service program in Dawuhan Village, Kademangan District, Blitar Regency, focused on the development of the micro, small, and medium enterprise (MSME) "Mbah Juki" cassava crackers, which faced significant challenges in pricing, production efficiency, and marketing. The primary objective of the program was to enhance participants' managerial and technical capacities through training in operational systems and pricing strategies. The methodology involved problem identification through surveys, training, direct mentoring, and periodic evaluations. The results demonstrated improved participant abilities in setting more strategic pricing, enhancing production efficiency, and effectively utilizing social media and packaging design to attract customers. Evaluations indicated significant improvements in efficiency and product competitiveness, contributing positively to business sustainability and local economic empowerment. Overall, the community service activities successfully met the established targets and had a positive impact on both the MSME and the local community.